Implementing a Love-Based Curriculum in Arabic Language Education: Insights from Ki Hajar Dewantara’s Educational Philosophy - Maskuri, Maskuri; Mukminin, Amirul; Sutaman, Sutaman; Zekyzak, Fathalla Mohammed Fathalla (Universitas Islam Negeri Jurai Siwo Lampung, 2025)
This study examines the conceptual integration of the “curriculum of love” into Arabic language learning through the lens of Ki Hajar Dewantara’s educational philosophy. In the Indonesian context, Arabic serves not only as a linguistic medium but also as a means of internalizing Islamic values and character education. Nevertheless, Arabic instruction has largely emphasized cognitive and technical aspects, often overlooking learners’ emotional and spiritual development. Employing a literature review method, this study analyzes national and international scholarly works published between 2010 and 2025 concerning affective pedagogy, character-based Arabic education, and Dewantara’s educational principles—ing ngarso sung tulodo, ing madyo mangun karso, and tut wuri handayani. The findings propose a conceptual model of Arabic learning that integrates linguistic competence with affective-spiritual growth, positioning teachers as empathetic facilitators. This model promotes reflective, contextual, and student-centered learning, offering a culturally grounded and humanistic contribution to Arabic language pedagogy.